THE TEACHERS’ PERCEPTION ON THE IMPLEMENTATION OF BILINGUAL PROGRAM OF SMP AND SMA DHARMA YUDHA PEKANBARU - Noviani Noviani; Dahnilsyah Dahnilsyah; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research analyses the teachers’ perception on the implementation of bilingual program of SMP and SMA Dharma Yudha Pekanbaru. The data was collected by giving a survey adapted on the Gonzales’s theory (2013) about level of satisfaction of teacher teaching in English. This research design is descriptive involving 31 bilingual teachers. All the teachers participated as respondents for this research. The conclusion of the study reveals that the bilingual teachers’ satisfaction category was high (2.77) from likert scale used (1-4).Key words: bilingualism, perception, implementation, satisfaction